Sanctions, Conflict Zones and the Repricing of Maritime Risk: Structural Implications for Specialty Insurance Markets - Patyrykin, Kirill; Dobrovolskiy, Daniil; Vasyukova, Lyudmila (Journal of Posthumanism, 2026)
Marine insurance is a very vital aspect in topping the maritime trade in the world as it offers financial safeguard against both operational and legal risk related to shipping. The marine insurance structures that were used in the past are mainly structured to cover physical and operational risks that include Cargo loss, shipwreck and accidents on the sea. The growing geopolitical threats and sanctions governments are also bringing about new legal and regulatory perspectives that have great impact on maritime risk evaluation. Government and international institutions sanction laws limit the activities of a trade, transaction of finances and insurance services relating to jurisdictions, organizations or a single individual. The marine insurers are required to therefore incorporate sanctions compliance in underwriting and in the writing of policies to be made sure that insurance coverage does not impact relevant legal frameworks. The paper will discuss the readjustment of the maritime risk through sanctions regimes and geopolitical conflict in the specialty insurance markets. The study utilizes doctrine legal study of sanctions laws in the maritime trade, stress simulation of portfolio by simulating the impact of geopolitical exposure on underwriting portfolios, and qualitative information of marine insurance experts. The results suggest that Sanctions laws and warring states have changed the maritime risk as an operational issue to a multifaceted legal and regulatory matter. To ensure that insurance contracts are legally enforceable and in compliance with the existing regulations, marine insurers are growing to include sanctions clauses and updated war risk exclusions in insurance agreements. It is also demonstrated that geopolitical instability affects premium pricing policies and capital deployment aspects in marine insurances markets. The study sheds light on the enforcement of tighter compliance regimes, explicit wording of the contract and the incorporation of geopolitical assessment of risk in the underwriting programs. These are developments that need to be done so that marine insurance markets remain stable and support international maritime trade within a new set of sanctions and geopolitical realities.